Low-temperature H2-SCR of NO on a novel Pt/MgO-CeO2 catalyst - Efstathiou, Angelos M.; Costa, Costas (My University, 2007)
The selective catalytic reduction of NO by H2 under strongly oxidizing conditions (H2-SCR) in the low-temperature range of 100–200 °C has been studied over Pt supported on a series of metal oxides (e.g., La2O3, MgO, Y2O3, CaO, CeO2, TiO2, SiO2 and MgO-CeO2). The Pt/MgO and Pt/CeO2 solids showed the best catalytic behavior with respect to N2 yield and the widest temperature window of operation compared with the other single metal oxide-supported Pt solids. An optimum 50 wt% MgO-50wt% CeO2 support composition and 0.3 wt% Pt loading (in the 0.1–2.0 wt% range) were found in terms of specific reaction rate of N2 production (mols N2/gcat s). High NO conversions (70–95%) and N2 selectivities (80–85%) were also obtained in the 100–200 °C range at a GHSV of 80,000 h−1 with the lowest 0.1 wt% Pt loading and using a feed stream of 0.25 vol% NO, 1 vol% H2, 5 vol% O2 and He as balance gas. Addition of 5 vol% H2O in the latter feed stream had a positive influence on the catalytic performance and practically no effect on the stability of the 0.1 wt% Pt/MgO-CeO2 during 24 h on reaction stream. Moreover, the latter catalytic system exhibited a high stability in the presence of 25–40 ppm SO2 in the feed stream following a given support pretreatment. N2 selectivity values in the 80–85% range were obtained over the 0.1 wt% Pt/MgO-CeO2 catalyst in the 100–200 °C range in the presence of water and SO2 in the feed stream. The above-mentioned results led to the obtainment of patents for the commercial exploitation of Pt/MgO-CeO2 catalyst towards a new NOx control technology in the low-temperature range of 100–200 °C using H2 as reducing agent. Temperature-programmed desorption (TPD) of NO, and transient titration of the adsorbed surface intermediate NOx species with H2 experiments, following reaction, have revealed important information towards the understanding of basic mechanistic issues of the present catalytic system (e.g., surface coverage, number and location of active NOx intermediate species, NOx spillover).
Keywords: H2-SCR; Lean de-NOx; NO reduction; NO TPD; Supported-Pt; Transient kinetics